Матеріали, присвячені 90-річчю НАН України (Наука та наукознавство, 2009)
Наведені матеріали, присвячені 90-річчю НАН України Приведены материалы, посвященные 90-летию НАН Украины Proceedings dedicated to the 90th anniversary of the National Academy of Sciences of Ukraine are presented